Eksplorasi Penguasaan Simbol dan Kosa Kata Matematika pada Guru Matematika - Fauzi, Azra; Arifuddin, Arifuddin (Lembaga Penelitian dan Pendidikan Mandala, 2021)
Exploration of Matthematical Symbol and Word Mastery on Mathematics Teacher. This research is a descriptive qualitative research that aims to explore the mastery of symbols and mathematical words in teachers. The subjects in this study were five mathematics teachers ini Lambitu District, Bima. Data collection techniques in this study are observation and interviews. Observations were made to observe the mastery of symbols and mathematical words when the teacher carried out the learning process. Interviews were conducted to obtain data on the factors that influence the mastery of symbols and mathematical words for teachers. Data analysis technique used are data reduction, data presentation, and make conclusions. The results showed that the overall mastery of symbols and mathematical words for teachers were good. There are only a few mistakes or errors that teachers make in the use of symbols and mathematical words. These mistakes or errors are caused by misconceptions and inaccuracies.